MDS-WLAN: Maximal Data Security in WLAN for Resisting Potential Threats - Latha P.H.; Vasantha R (Institute of Advanced Engineering and Science, 2015)
The utmost security standards over Wireless Local Area Network (WLAN) are still an unsolved answer in research community as well as among the commercial users. There are various prior attempts in proposing security of WLAN that lacks focus on access point and is found to be quite complex implementation of cryptography. The proposed paper presents a novel, simple, and yet robust technique called as MDS-WLAN i.e. maximal data security in WLAN. The system is evaluated over laboratory prototype and mitigation measures are drawn for resisting wormhole attack, Sybil attack, and rogue access point issue in WLAN. The outcome of the MDS is compared with conventional AES and SHA that shows optimal communication performance and highest data security.